Perancangan Mekanisme Pelurusan Kawat SAE 304 (UNS S30400) Galvanized Menggunakan Prinsip Pengerolan - Herman Susanto; Sunardi Tjandra (Universitas Muhammadiyah Sidoarjo, 2020)
Wire is a complement material on the manufacturing product. Therefore, the wire processes usually bestowed to the middle-low industry. Cutting and straightening wire processes are the most basic process for wire materials. In the middle-small industry, demand of wire materials is 150 kg per day. Seeing this potential, the design of a wire straightening mechanism for middle-low industries is necessary to maximize productivity. The main purpose of wire straightening mechanism design is calculating roll diameters and placement to obtain appropriate rolling force. In designing this wire straightening mechanism, the raw materials are used 3 mm SAE 304 (UNS S30400) Galvanized. The rolling method used in this mechanism is Three-Roll Bending. The empirical method is used on this analysis. Based on the analytical results, roll used on this mechanism are 5 pieces or equal with 3 cycle of rolling process with 40 mm of diameters. The vertical gap between center of rolls is 41.5 mm with 54 mm horizontal gap. Rolling force produced by the analytical roll dimension is 1608.69 N/cycle and that’s enough to give plastic deformation on the 3 mm SAE 304 (UNS S30400) Galvanized wire.